Magnetic PSA-Fe3O4@C 3D mesoporous microsphere as anode for lithium ion batteries. (10th January 2016) - Zhang, Wanli; Hou, Xianhua; Shen, Jiadong; Hu, Shejun; Ru, Qiang; Lam, Kwok-ho
Abstract: Fe3 O4 has long been regarded as one of the most promising anode materials for lithium ion batteries due to its high theoretical capacity, low cost, and nontoxic properties. Here, we report a facile hydrothermal way to perform carbonization of poly (ST-AN) (PSA) to obtain a PSA-Fe3 O4 @C3Dmesoporousmicrosphere. (*) Its electrochemical performance as an anode material was evaluated by cyclic voltammetry (CV) and galvanostatic charge/discharge experiments. The PSA-Fe3 O4 @C electrode delivers a capacity of 1130 mA h g −1 at 0.5 C, in contrast to that of the CA (Citric Acid)-Fe3 O4 @C (1111 mA h g −1 ) and Fe3 O4 (817 mA h g −1 ). The improvements can be attributed to the unique composition and microstructure that endow the electrode with large contact area between material and electrolyte, short diffusion path for lithium ions transportation in the active material, low electron transfer resistance from a current collector to the active material, and large buffering space for volume change during charging/discharging process.